A Framework for the Impact of Individual and Contextual Factors on Programmer’s Creativity: A Study in Offshore Software Development Outsourcing based Companies of Pakistan - AMIN, AAMIR (2018)
Programmer perform one of the most creative tasks, of writing codes, in software development. However, the existing research work on creativity in software engineering has largely ignored programmer’s creativity and what factors can promote or hamper it.